Українська дипломатична служба 1917–1921 рр.: формування інструментарію публічної й культурної дипломатії - Матяш, І. (Український історичний журнал, 2021)
Мета статті полягає у з’ясуванні форм і засобів формування позитивного образу України як незалежної держави та інструментарію публічної й культурної дипломатії. Методологія дослідження спирається на принципи науковості, історизму, системності. Для виявлення та класифікації джерел, повноти й достовірності викладених у них
фактів застосовано методи джерелознавчої критики; для дослідження інструментарію
української дипломатії у сфері формування уявлень зарубіжних суспільств про українців,
їхню історію та культуру – метод імагології. Наукова новизна результатів дослідження
полягає в реконструкції витоків інституціалізації публічної та культурної дипломатії в
діяльності дипломатичної служби, формування інструментарію пропаґанди української
ідеї, застосування засобів мистецтва для створення позитивного уявлення зарубіжного
суспільства про Україну. Висновки. Із метою поширення у світі інформації про Україну
і протидії антиукраїнській пропаґанді було сформовано інституційну структуру, яка охоплювала
відповідні підрозділи у МЗС, інформаційні бюро, прес-бюро диппредставництв.
Особливість реалізації завдань української дипломатії у сфері досягнення присутності
в інформаційному полі країн світу полягала в державному фінансуванні та міжвідомчій
взаємодії й координації діяльності з урядами, громадськістю, українською еміґрацією.
З цією метою було апробовано такі інструменти, як публікації/інтерв’ю послів у зару-
біжній пресі, друк періодичних бюлетенів та серійних видань про Україну, проведення
курсів вивчення української мови, науково-популярних лекторіїв, книжкових виставок,
виявлення зарубіжної україніки, організація виступів мистецьких колективів та зйомок
кінофільмів. The purpose of the study is to determine the core directions and means of the
creation of a positive image of Ukraine as an independent state and a tool of public and cultural
diplomacy in the activity of the Diplomatic Service. The research methodology is based on the
principles of scientificity, historicism, systematization as well as general and particular scientific
research methods. The methods of source criticism, inter alia, are used to identify and classify
sources, completeness and reliability of the facts contained therein; the method of imagology allows
exploring the tools of Ukrainian diplomacy in the field of shaping foreign societies’ perceptions of
the Ukrainians, their history and culture. The scientific novelty of the research results is approved
by the reconstruction of the institutionalization origins of public and cultural diplomacy in the
activity of the Diplomatic Service of Ukraine, the formation of tools for promoting the Ukrainian
idea, the use of art to create a positive image of Ukraine. Conclusions. With the aim of information
dissemination about Ukraine in the World and confronting anti-Ukrainian propaganda, an
institutional structure was built that included the relevant units in the central office of the Ministry
of Foreign Affairs, the information and press bureaus of diplomatic missions. The peculiarity of
the implementation of the tasks of Ukrainian diplomacy in the sphere of achieving a presence in
the global information area was public funding, interagency cooperation, and activity coordination
with governments, civil society, Ukrainian emigration of host countries. To complete these tasks,
there were such tools as the placement of articles and interviews of the ambassadors and senior
diplomats on the pages of foreign press, the publication of periodical bulletins and serial collections
about Ukraine, its history and culture, the organization of popular scientific lectures, book
exhibitions, concerts of Ukrainian creative troupes, and also teaching Ukrainian language courses,
detecting foreign Ukrainika, and film showings.